MICROSTRUCTURAL AND MECHANICAL PROPERTIES AL 6061 PROCESSED BY COLD ROLLING AND AGING - Ahmad Ali Alhamidi; Mirnawati Dewi (VANOS Journal of Mechanical Engineering Education, 2018)
An Alumunium alloy 6061was produced by cold rolling and subsequently aging. Cold rolling is used for reducing grain size and aging is used for producing second-phase, thus improving hardness, strength and wear resistance. In the present paper, a process through cold rolling with reduction of 50%, 60% and 70% in thickness then aged at 2000C for 1.800, 3.600, 5.400, 7.200 and 10.800 sec. Microstructural analysis shows that the grain morphology consists of equaxied grain for as-received samples and elongated grain for sample after cold roll and aging. X-Ray Diffraction (XRD) analysis showed peaks phases in Al 6061 after cold rolled and aging. Hardness measurements showed that combination between small grain size and presence of second-phase led to a significant increase in the hardness. Maximum hardness of 121 HBN is achieve for sample after cold roll 70% and aged for 5400 second. The wear resistance testing showed that lost particles of 6,209951 x 10-6 mm3/mm for received sample and 4,775436 x 10-6 mm3/mm for sample after aging process. It is showed that high hardness related to increase the wear resistance. It is reasonable that the presence of second phases are function as obstacle for dislocation movement.